PANDANGAN ULAMA KABUPATEN PONOROGO TERHADAP PERNIKAHAN DINI: Studi Kasus Pernikahan Dini di Kecamatan Badegan Kabupaten Ponorogo - Dwi Astuti Furi (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2020)
Early marriage or marriage at a young age is an inner and outer bond that is carried out by a young man or woman who has not yet reached the ideal level to make a marriage, in other words that the marriage is being done before adulthood age. Early marriage still often occurs in Badegan District, Ponorogo. Conducting a field reseach regarding the views of Ponorogo ulama (religious scholars) about early marriage, data collection is done through direct interviews. Then the data is re-examined (editing), systematically arranged in the form of exposure (organizing) and analyzed in accordance with the discussion by using rules, theory and proposition so that it finds valid results. From the data collection, discussion with descriptive analysis method was carried out, namely describing the problem of information that would be used as the object of discussion in order to get a view and legal settlement of the Ponorogo scholars as the end of the research. From this study it can be concluded that (1) Early marriage from the perspective of ulama in Ponorogo according to Fiqh perspective is legal, while in the eyes of positive law in Indonesia, it should be avoided; (2) The basis of the argumentation of scholars in Ponorogo Regency in judging early marriage is naqli and aqli. The naqli basis used in establishing the validity is the proposition of the text of a hadith which narrates that Rasulullāh married Aisha at the age of 9, and the basis of the aqli used is benefit to avoid greater harm. As contained in the Marriage Law (UU Pokok Perkawinan) No. 1 of 1974 that limits the age of marriage with the aim of avoiding harm.